Development of a molecular method for testing the effectiveness of UV systems on-site. (15th December 2017) - Nizri, Limor; Vaizel-Ohayon, Dalit; Ben-Amram, Hila; Sharaby, Yehonatan; Halpern, Malka; Mamane, Hadas
Abstract: We established a molecular method for quantifying ultraviolet (UV) disinfection efficacy using total bacterial DNA in a water sample. To evaluate UV damage to the DNA, we developed the "DNA damage" factor, which is a novel cultivation-independent approach that reveals UV-exposure efficiency by applying a simple PCR amplification method. The study's goal was to prove the feasibility of this method for demonstrating the efficiency of UV systems in the field using flow-through UV reactors. In laboratory-based experiments using seeded bacteria, the DNA damage tests demonstrated a good correlation between PCR products and UV dose. In the field, natural groundwater sampled before and after being subjected to the full-scale UV reactors was filtered, and the DNA extracted from the filtrate was subjected to PCR amplification for a 900-bp fragment of the 16S rRNA gene with initial DNA concentrations of 0.1 and 1 ng/μL. In both cases, the UV dose predicted and explained a significant proportion of the variance in the log inactivation ratio and DNA damage factor. Log inactivation ratio was very low, as expected in groundwater due to low initial bacterial counts, whereas the DNA damage factor was within the range of values obtained in the laboratory-based experiments. Consequently, the DNA damage factor reflected the true performance of the full-scale UV system during operational water flow by using the indigenous bacterial array present in a water sample. By applying this method, we were able to predict with high confidence, the UV reactor inactivation potential. For method validation, laboratory and field iterations are required to create a practical field calibration curve that can be used to determine the expected efficiency of the full-scale UV system in the field under actual operation. Graphical abstract: Highlights: Molecular method to quantify UV disinfection effectiveness in water was established. PCR product reduction was correlated with UV dose. DNA damage factor can be used when log inactivation may not be indicative. The method challenges known validations.